Pengaruh Model Problem Based Learning Berbantuan Media Visual Terhadap Hasil Belajar Siswa Pada Materi Dampak Sosial Informatika - Pakaja, Jemmy A.; Latief, Mukhlisulfatih; Mangundap, Kirana Zahra M. (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by visual media on students' learning outcomes in the topic of Social Impacts of Informatics. The background of this research stems from the low learning outcomes among students due to the continued use of conventional teaching methods, which have not effectively fostered critical thinking and problem-solving skills. The study was conducted at MTS Negeri 1 Kota Gorontalo using a quasi-experimental method with a Nonequivalent Control Group Design. The subjects consisted of two classes: class VIII-3 as the control group and class VIII-5 as the experimental group, each comprising 36 students. The research instrument consisted of 20 multiple-choice questions used for both pre-test and post-test. Data analysis using normality tests, homogeneity tests, and hypothesis testing (paired sample t-test and independent sample t-test) revealed a significant improvement in the learning outcomes of students taught using the PBL model assisted by visual media. The average post-test score in the experimental group reached 84.17%, significantly higher than the control group’s average of 38.47%. Thus, it can be concluded that the implementation of the PBL model assisted by visual media has a significant effect on students' learning outcomes in the topic of Social Impacts of Informatics.Kata kunci: Dampak Sosial Informatika, Hasil Belajar, Media Visual, Problem Based Learning